2024
DOI: 10.7554/elife.93450
|View full text |Cite
|
Sign up to set email alerts
|

Adipokinetic hormone signaling mediates the enhanced fecundity of Diaphorina citri infected by ‘Candidatus Liberibacter asiaticus’

Jiayun Li,
Paul Holford,
George Andrew Charles Beattie
et al.

Abstract: Diaphorina citri is the primary vector of the bacterium, ‘ Candidatus Liberibacter asiaticus’ ( C Las) associated with the severe Asian form of huanglongbing. C Las-positive D. citri are more fecund than their C Las-negative counterparts and require extra energy expenditure. Therefore, understanding the molecular mechanisms linking metabolism and reproduction is of particular importance. In this present study, we found adipokinetic hormone ( DcAKH ) and its receptor ( DcAKHR ) were essential for increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Previous studies have revealed a mutualistic relationship in which C Las infection boosts the fitness of D. citri by increasing its ability to produce large numbers of offspring (fecundity), but the molecular dynamics driving this interaction were not fully understood ( Pelz-Stelinski and Killiny, 2016 ; Ren et al, 2016 ). Now, in eLife, Yijing Cen, Xiaoge Nian and colleagues from South China Agricultural University, Shaoguan University, and Western Sydney University – including Jiayun Li as first author – report results that shed light on this interaction at the molecular level ( Li et al, 2024 ).…”
mentioning
confidence: 99%
“…Previous studies have revealed a mutualistic relationship in which C Las infection boosts the fitness of D. citri by increasing its ability to produce large numbers of offspring (fecundity), but the molecular dynamics driving this interaction were not fully understood ( Pelz-Stelinski and Killiny, 2016 ; Ren et al, 2016 ). Now, in eLife, Yijing Cen, Xiaoge Nian and colleagues from South China Agricultural University, Shaoguan University, and Western Sydney University – including Jiayun Li as first author – report results that shed light on this interaction at the molecular level ( Li et al, 2024 ).…”
mentioning
confidence: 99%